Variability of day-to-day pulsatility index change in children with cerebral malaria - Jordan, Jeremy; O’Brien, Nicole; Li, Peng; Musungufu, Davin Ambitapio; Ekandji, Robert Tandjeka; Mbaka, Jean Pongo; Mayindombe, Ludovic; Giresse, Buba; Phiri, Tusekile; June, Sylvester; Gushu Co, Montfort Bernard; Tshimanga, Taty; et al. (Frontiers in Neurology, 2024)
IntroductionCerebral malaria (CM) is a devastating disease and better understanding of etiologies of the resulting neurologic injury is needed. The purpose of this study is to describe the day-to-day (DTD) pulsatility index (PI) change measured by transcranial Doppler ultrasound (TCD), a novel measure of cerebral and vascular changes, in children with CM.MethodsA retrospective analysis of 122 children in sub-Saharan Africa with CM and 3 or more sequential TCD measurements was performed. Variability of DTD PI change was calculated as a measure of changes in vasculature overtime. Neurologic outcome was determined by the Pediatric Cerebral Performance Category (PCPC) score, a measure of neurologic function.ResultsOf the 122 participants, 77.9% had a good neurologic outcome (no neurologic sequelae), and 22.1% had a poor outcome (neurologic sequelae or died). Patients who had a poor neurologic outcome had higher levels of variability of DTD PI change in the right middle cerebral artery (MCA) (0.14 ± 0.21) and left MCA (0.17 ± 0.41) compared to those who had a good neurologic outcome (0.1 ± 0.1 and 0.11 ± 0.19, respectively). A higher variability of both left and right MCA DTD PI change was also associated with higher brain volume assessed through neuroimaging.DiscussionVariability of DTD PI change may provide early prognostic information regarding PCPC outcomes and brain volume changes seen in CM patients. Expanded research on pathophysiologic contributors to variability of DTD PI changes in children with CM is warranted.